Effectiveness of instrument assisted soft tissue mobilization (IASTM) and muscle energy technique (MET) on post-operative elbow stiffness: a randomized clinical trial - Bhosale, Prajakta; Kolke(PT), Sona (The Journal of manual & manipulative therapy, 2023)
Stiffness is a common complication following trauma and surgeries around the elbow, which can result in upper limb functional disabilities. Soft tissue mobilization techniques such as Instrument-assisted Soft Tissue Mobilization (IASTM) and Muscle Energy Technique (MET) have limited evidence in elbow rehabilitation. This study aimed to compare their effects on postoperative elbow stiffness. 26 subjects were recruited (13 each group) with postoperative elbow stiffness (minimum 6 weeks post surgery) and randomly allocated in two groups: IASTM and MET. Pain [Numeric Pain Rating Scale NPRS)], ROM (Goniometer), and Function [Disability of Arm, Shoulder and Hand (DASH) and Patient-Specific Functional Scale (PSFS)] were assessed at baseline and post-intervention. The data of 26 subjects were analyzed and both groups significantly improved in outcome scores post-intervention. The improvements in ROM and function between groups were comparable, but NPRS and PSFS showed greater improvement in the IASTM group (p < 0.05). IASTM and MET were both effective in improving outcomes in postoperative elbow stiffness. IASTM was more effective in improving pain and patient-specific function.